PP19 Primary care streaming in emergency departments- contexts and mechanisms associated with perceived effectiveness outcomes: a realist evaluation. Issue 9 (19th August 2021) - Edwards, Michelle; Cooper, Alison; Davies, Freya; Stevens, Andrew Carson; Edwards, Adrian; Hughes, Thomas; Snooks, Helen; Anderson, Pippa; Porter, Alison; Evans, Bridie; Dale, Jeremy; Cooke, Matthew; et al.
Abstract : Background: Recent policy has encouraged emergency departments (EDs) to deploy nurses to stream patients from the ED front door to GPs working in a separate GP service operating within or alongside an ED. We aimed to describe mechanisms relating to effectiveness of streaming in different primary care service models identified in EDs. We explored perceptions of whether patients were perceived to be appropriately streamed to emergency care, primary care, other hospital services or community primary care services; and effects on patient flow (waiting times and length of stay in the ED); and safe streaming outcomes. Methods: We used realist evaluation methodology to explore perceived streaming effectiveness. We visited 13 EDs with different primary care service models (purposively selected across England & Wales; 8 streamed primary care patients to a primary care clinician) and carried out observations of triage/streaming and patient flow and interviews with key members of staff (consultants, GPs, nurses). Field notes and audio-recorded interviews were transcribed and analysed by creating context, mechanism and outcome configurations to refine and develop theories relating to streaming effectiveness. Results: We identified five contexts (nurses' knowledge and experience, streaming guidance, teamwork and communication, operational management and strategic management) that facilitated mechanisms that influenced the effectiveness of streaming (streaming to an appropriate service, patient flow, delivering safe care). We integrated a middle range psychological theory (cognitive continuum theory) with our findings to recommend a focus for training nurses in streaming and service improvements. Conclusions: We identified key mechanisms relating to the effectiveness of primary care streaming in different models of service. We recommend a collaborative approach to service development, guidance and training (including input from ED clinicians and primary care clinicians) and a range of training strategies that are suitable for less experienced junior nurses and more experienced senior nurses and nurse practitioners.